Determinan Indeks Pembangunan Manusia Kawasan Timur Indonesia (KTI) - Ayu Wandirah; Joko Setyono (Jurnal Magister Ekonomi Syariah, 2024)
This paper examines how government expenditure affects the education and health sectors, economic growth, and labor force on HDI in 13 provinces in the Eastern Region of Indonesia (KTI) for 2015-2022. Using panel data regression, this paper studies whether the human development index correlates to government expenditure on the education and health sectors, economic growth, and the labor force in the province of KTI. The study's findings revealed that all exogenous variables in this paper were important factors that influenced human development in KTI during the 8-year observation period. This shows that the government has succeeded in improving the welfare of its people, which is reflected in the value of HDI in each KTI province which has increased in recent years. However, the government still has to continue striving for human development to improve its people's quality of life and standard of living.